دور وسائل التواصل الاجتماعي في دعم فكر ريادة الأعمال: مقاربة باستخدام تقنيات تعلم الألة لطلبة جامعة الوادي - بلول عماد; بكادي أكرم (جامعة الوادي University Of Eloued, 2025)
"هدفت هذه الدراسة الى معرفة الى أي مدى تساهم وسائل التواصل الاجتماعي في دعم فكرة ريادة الاعمال. ومن اجل معالجة إشكالية البحث استخدمنا المنهج الوصفي، واستخدمنا الاستبيان الالكتروني للحصول على البيانات من مجتمع الدراسة المتمثلة في طلبة جامعة الشهيد حمه لخضر الوادي، وتحصلنا على عينة قوامها 543 استبيان صالح للدراسة، واستخدمنا خوارزمية الغابة العشوائية لتقدير النماذج عن طريق البرمجة R وRStudio. وتوصلنا الى عدة نتائج أهمها: وسائل التواصل الاجتماعي تساهم بشكل غير مباشر في تعزيز التفكير الريادي لدى طلبة جامعة الوادي، تعتبر الدافعية في اغلب النماذج متغير مستقل في التأثير على التفكير الريادي المرتبط باستخدام وسائل التواصل الاجتماعي، اظهرت نماذج الغابات العشوائية دقة متوسطة نظرا لطبيعة الدراسة، تعتبر المتغيرات الديموغرافية ذات اهمية منخفضة حيث لا يميز العمر ولا الجنس في التفكير الريادي المرتبط باستعمال وسائل التواصل الاجتماعي لدى طلبة جامعة الوادي. وأوصت الدراسة الى العديد من التوصيات أهمها: دمج ثقافة الريادة في المناهج الدراسية وربطها بالاستخدام الفعال لوسائل التواصل الاجتماعي، تنظيم ورشات تدريبية دورية حول كيفية استثمار مواقع التواصل في الترويج والتسويق، دعم المبادرات الرقمية الطلابية التي ظهرت وسائل التواصل الاجتماعي من خلال تمويل أو احتضان، إنشاء نوادي جامعية لريادة الأعمال. "This study aimed to determine the extent to which social media contributes to supporting entrepreneurship. To address the research problem, we used a descriptive approach and an electronic questionnaire to obtain data from the study population, represented by students at the University of Martyr Hama Lakhdar El Oued. We obtained a sample of 543 valid questionnaires for the study. We used the random forest algorithm to estimate models using R and RStudio programming. We reached several results, the most important of which are: Social media indirectly contributes to enhancing entrepreneurial thinking among Wadi University students. In most models, motivation is considered a pivotal mediating variable influencing entrepreneurial thinking associated with the use of social media. Random forest models showed low accuracy due to the nature of the study. Demographic variables are considered of low importance, as neither age nor gender distinguishes in entrepreneurial thinking associated with the use of social media among Wadi University students. The study made several recommendations, the most important of which are : integrating entrepreneurship culture into academic curricula and linking it to the effective use of social media, organizing periodic training workshops on how to invest in social media for promotion and marketing, and supporting student digital initiatives that emerged on social media by funding or incubating the establishment of university entrepreneurship clubs."
Keywords: ريادة الأعمال،; وسائل التواصل الاجتماعي; Entrepreneurship; Social Media